Analisis Penerapan Pajak Pertambahan Nilai Atas Transaksi Ekspor Impor Jasa Freight Forwarding Pada Pt. IFB Indonesia Tahun 2021 - Monika Silaen; Rahadi Pratomo Singgih (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
In general, freight forwarding services are divided into four namely customs services, pure transportation management services, trucking services, and warehousing services. In practice, the forwarder (PT IFB Indonesia) cooperates with third parties. The third parties include transportation companies (land, sea, and air transportation), and loading and unloading companies. The tax law already regulates the application of VAT on freight forwarding services but there is no detailed explanation of its implementation so that forwarders have a little difficulty in calculating the tax base. The problem that arises is the determination of the basis for imposition of taxes on freight forwarding services so that the taxes collected by the forwarder from the consumer/goods owner are in accordance with the applicable regulations. The results of this study show that forwarders have different understandings regarding the application of tax payable, especially VAT, on their business. The author suggests that the government make detailed rules regarding VAT on freight forwarding services and campaign for any new regulations and laws.